Scaling Up Social Problems: Strategies for Solving Social Work's Grand Challenges. (March 2017) - Rodriguez, Maria Y.; Ostrow, Laysha; Kemp, Susan P.
The Grand Challenges for Social Work Initiative aims to focus the profession's attention on how social work can play a larger role in mitigating contemporary social problems. Yet a central issue facing contemporary social work is its seeming reticence to engage with social problems, and their solutions, beyond individual-level interventions. Social work research, we contend, must more consistently link case and cause, iteratively developing processes for bringing micro-, mezzo-, and macrostreams of information together. We further argue that meaningful engagement with the initiative requires social work scholars and practitioners to actively scale up practice and research inquiry. We detail two key strategies for employing a scaled-up social work practice and research ethos: (a) employing a critical economic lens and (b) engaging with diverse publics. As proof of concept for these arguments, we offer an early example of progressive era social workers scaling up responses to a pressing social issue: infant mortality.